Intertemporal substitution and recursive smooth ambiguity preferences - Jianjun Miao; Takashi Hayashi (Theoretical Economics, 2011)
In this paper, we establish an axiomatically founded generalized recursive smooth ambiguity model that allows for a separation among intertemporal substitution, risk aversion, and ambiguity aversion. We axiomatize this model using two approaches: the second-order act approach à la Klibanoff, Marinacci, and Mukerji (2005) and the two-stage randomization approach à la Seo (2009). We characterize risk attitude and ambiguity attitude within these two approaches. We then discuss our model's application in asset pricing. Our recursive preference model nests some popular models in the literature as special cases.
Keywords: D80; D81; D90; 330; Ambiguity; ambiguity aversion; risk aversion; intertemporal substitution; model uncertainty; recursive utility; dynamic consistency